Effect of super olein and sunflower oil on the rheological properties of chocolate syrup - Nazaruddin Ramli; Foo, Shih Ying (Universiti Kebangsaan Malaysia, 2011)
This study was carried out to determine the effect of super olein (POo) and sunflower oil (SFO) on the rheological properties of chocolate syrup. The formulation of chocolate syrup was modified from that used in a preliminary study consisting of 49.1% water, 30% sugar, 15% cocoa powder, 5% vegetable fats (POo and SFO), 0.5% lecithin and 0.4% vanilla flavour. The rheology of chocolate syrup was measured at a shear rate of 0.01-60 s-1 using a rotational rheometer equipped with a parallel plate at 4°C and 25°C. The shear stress and shear rate data were entered into the Power Law model to determine the apparent viscosity, flow behaviour index (n) and consistency index (K) of the chocolate syrup. In this study, the apparent viscosity of the chocolate syrup was determined at a shear rate of 30 s-1. The apparent viscosity of POo chocolate syrup was the highest at 14.62 ± 1.97 Pa.s (4°C) and 3.91 ± 0.21 Pa.s (25°C), followed by SFO chocolate syrup, with apparent viscosities of 5.42 ± 0.40 Pa.s (4°C) and 1.203 ± 0.076 Pa.s (25°C). The apparent viscosity of Hershey’s chocolate syrup was the lowest, at 2.15 ± 0.070 Pa.s (4°C) and 0.6734 ± 0.027 Pa.s (25°C). All of the chocolate syrups exhibited shear-thinning behaviours with n<1 at 4°C and 25°C. The consistency index of chocolate syrup increased in the order of KHershey<KSFO<KPOo at 4°C and 25°C. For sensory evaluation, it was found that POo and SFO chocolate syrups were preferred by the panellists over Hershey’s syrup (p<0.05). There was no significant difference between the POo and SFO chocolate syrups with respect to panellists’ preferences. In conclusion, POo and SFO can be potentially utilised in the preparation of chocolate syrups.